Download presentation

Presentation is loading. Please wait.

1
**Bell Ringer – solve each for x.**

7) 3x + 5 = 10x -9

2
**Steps to Solving an Equation**

1) Simplify each side (expression) of equation separately. (distribute, combine like terms) 2) Remove fractions if desired (multiply everything on both sides by the Least Common Multiple – common denominator) 3) Move variable term to one side (add or subtract) 4) Eliminate constant (add or subtract) 5) Eliminate coefficient (divide or mult. by recip.)

3
**Examples: Solve each for x**

1) 10(x-4) = 4(x+4) + 4x 2) ½ x + ⅓x = 10

4
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1)

5
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side

6
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute

7
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side

8
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side -15 = 3x + 6 subtracted 3x

9
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side -15 = 3x + 6 subtracted 3x eliminate constant -21 = 3x

10
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side -15 = 3x + 6 subtracted 3x eliminate constant -21 = 3x subtracted 6

11
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side -15 = 3x + 6 subtracted 3x eliminate constant -21 = 3x subtracted eliminate coefficient

12
Think Aloud Explain out loud what to do, how and why at each step of the process. 3(x – 5) = 6 (x + 1) Simplify each side 3x -15 = 6x + 6 Distribute -3x -3x Move variables to 1 side -15 = 3x + 6 subtracted 3x eliminate constant -21 = 3x subtracted eliminate coefficient -7 = x divided by 3

13
Student think aloud # 1 5w + 2 = 2w + 5

14
Student think aloud #2 -4(x + 2) = 3( x – 4)

15
**Process Analysis A written think aloud in paragraph form.**

Solve problem on top of paper. After EACH step, write a sentence explaining WHAT you did, HOW and WHY. 12(x + 3) = 2(x + 5) – 3x

Similar presentations

© 2017 SlidePlayer.com Inc.

All rights reserved.

Ads by Google